1990
DOI: 10.1088/0957-0233/1/2/006
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A new tensile tester has been developed for use in the scanning electron microscope to deform a specimen of 100 mm length by a force as high as 5000 N during microscopic investigation. The tensile force is induced by the hydraulic loading system. The force and the elongation of the specimen are measured and controlled by a computer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They screened over 200 polymers and found onepoly(acrylamidoxime), a copolymer of carboxylate and amidoxime monomers -that was stable and selective enough to extract uranium at pH 8.3, although it also has a high affinity for other ions, in particular vanadium, which is present at much higher concentrations. 2 The amidoxime monomer acts as the ligand, binding uranyl ions and, although it is not clear why, the researchers found that the carboxylate monomer also seems to play a vital role in enabling the reaction.…”
mentioning
confidence: 99%
“…They screened over 200 polymers and found onepoly(acrylamidoxime), a copolymer of carboxylate and amidoxime monomers -that was stable and selective enough to extract uranium at pH 8.3, although it also has a high affinity for other ions, in particular vanadium, which is present at much higher concentrations. 2 The amidoxime monomer acts as the ligand, binding uranyl ions and, although it is not clear why, the researchers found that the carboxylate monomer also seems to play a vital role in enabling the reaction.…”
mentioning
confidence: 99%